A Randomized Trial of Human Papillomavirus Self-Sampling as an Intervention to Promote Cervical Cancer Screening Among Women With HIV. Issue 2 (April 2016) - Murphy, Jeanne; Mark, Hayley; Anderson, Jean; Farley, Jason; Allen, Jerilyn
Abstract : Objective: Women living with HIV experience higher risk of cervical cancer, but screening rates in the United States are lower than recommended. The purpose of this study was to examine whether an intervention using self-sampling of cervicovaginal cells for human papillomavirus (HPV) with results counseling would increase cervical cytology ("Pap") testing among women with HIV. Materials and Methods: This was a randomized controlled trial to test the effectiveness of an intervention of self-sampling for HPV and results counseling. Participants were 94 women older than 18 years, with HIV infection, attending an HIV clinic for a primary care visit, whose last cervical cancer screening was 18 months or more before baseline. Women were assigned to the intervention or information-only group. The primary outcome was completion of cervical cytology testing within 6 months of baseline. The secondary outcome was the women's perceived threat of developing cervical cancer. Results: A total of 94 women were enrolled and analyzed in the study. The cytology completion rate overall was 35% by 6 months from baseline. There were no differences in comparing HPV-positive with HPV-negative women nor comparing them with the information-only group. In the intervention group, a positive HPV test increased perceived threat of cervical cancer. Conclusions: The intervention did not improve cytology test attendance, although education about HPV and cervical cancer risk as part of study procedures was associated with testing for 35% of this group of women whose previous cytology occurred an average of 3.6 years before the baseline appointment. Self-sampling for HPV testing was feasible. Abstract : A randomized controlled trial testing HPV self-sampling in women with HIV showed increased perceived threat of cervical cancer but no increase in follow-up cytology testing.